Manejo do solo e plantas de cobertura de inverno para o cultivo da soja em área de arroz irrigado - Fin, Silvana Spaniol (2017)
In Rio Grande do Sul state, the Alfisols areas are predominantly cultivated with irrigated rice, however, the monoculture of rice can complicate the use of these areas for rice crop. An alternative to this is the use of crop rotation. The soybean is a crop that may be used in rotation with irrigated rice, but due some soil characteristics, such as: poor drainage, low hydraulic conductivity and compacted layer present in the soil sub-surface, the soybean yield is usually limited especially in drought years. Accordingly, the objective of this study was to evaluate the duration of mechanical interventions, as soil scarification and raised bed, associated to cover plants during winter season, by means of physical indicators, hydric and oxygen deficiency index, agronomic characteristics and soybean grain yield in lowlands. The experiment was performed in the Lowland Experimental Area of the Federal University of Santa Maria-RS, during 2015/16 growing season. The treatments were composed by two factor. The factor A were composed by tillage systems: ES14 – Soil scarification in November of 2014; ES15 – Soil scarification in November of 2015; MI14 – raised bed built in November of 2014; MI15 – raised bed build in November of 2015. The D factor was applied during the winter, composed by winter fallow, oat, ryegrass and wheat as soil cover plants. During period from November 2015 up to April 2016, it was grown soybean on the yillage systems. Based on the results obtained, the effect of cover plants were not detected after an unique crop season, on the maintenance of alteration of the soil physical attributes. The level of remaining ryegrass straw of 3900 kg ha-1 verified in the present study reduces an initial soybean plantas population. Changes in the density, total porosity and soil resistance to mechanical penetration, promoted by deep tillage are noticeable by at least 18 months. This persistence reflect in the soybean grain yield for a second harvest. The raised bed and deep tillage realized in the same seeding period provides less occurrence of oxygen deficiency and greater nodulation, resulting in a higher yield of soybean grains in irrigated rice area.